Histomorphometric Changes of The Parietal Cell of The Stomach with Age - A Postmortem Study - Begum, Gul Newaz; Nurunnabi, Abu Sadat Mohammad; Shahriah, Sunjida; Rayhan, Khandaker Abu; Begum, Mahamuda (Journal of Bangladesh Society of Physiologist, 2014)
Background: The quantity of acid produced by the stomach correlates with the functional capability and number of parietal cell mass. Researchers have found that the number of parietal cells tends to increase with advancing age in different population-based studies. Objective: A cross-sectional descriptive type of study was designed to see the variation in the number and diameter of the parietal cells of the stomach with advancing age in Bangladeshi people. Methods: The present study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2005 to June 2006, based on collection of 60 human stomachs from the unclaimed dead bodies that were under examination in the morgue of Dhaka Medical College, Dhaka. The samples were divided into three age-groups including group A (2-16 years), group B (17-22 years) and group C (23-65 years). A total of 8 relatively fresh samples from group A, 8 from group B and 14 from group C were selected for histological study. Then best prepared histological slides from each group were taken and examined under the light compound microscope to determine the number per sq. mm and average diameter of the parietal cells by using the ocular micrometer. Results: The number of parietal cells per square mm of microscopic fields were found 1197.88±73.34 in group A, 1362.25±55.67 in group B and 1615.57±123.57 in group C. The difference between group A & B, B & C and A & C were statistically significant. The average diameter of the parietal cells were found 14.44±1.58ìm, 16.87±0.48ìm, 17.67±1.28ìm in group A, B and C respectively. The difference between group A & B and A & C were statistically significant. Conclusion: The number of the parietal cells increases with age, even in old age. However, the diameter of the parietal cell increases up to the 3rd decade of life and then remains static. DOI: http://dx.doi.org/10.3329/jbsp.v8i2.18660 Bangladesh Soc Physiol. 2013, December; 8(2): 89-93